Do co-worker networks increase or decrease productivity differences? An agent-based model - László L\~orincz (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
Do labor mobility, and co-worker networks contribute to convergence or divergence between regions? Based on the previous literature, labor mobility contributes to knowledge transfer between firms. Therefore, mobility may contribute to decreasing productivity differences, while limited mobility to sustaining higher differences. The effect of co-worker networks, however, can be twofold in this process. They transmit information about potential jobs, which may enhance mobility of workers, even between regions, and this enhanced mobility may contribute to levelling differences. But if mobility between regions involves movement costs, co-worker networks may concentrate locally that may contribute to persistence of regional differences. In this paper we build an agent-based model of labor mobility across firms and regions with knowledge spillovers that reflects key empirical observations on labor markets. We analyze the impact of network information provided about potential employers in this model and find that it contributes to increasing inter-regional mobility, and subsequently to decreasing regional differences. We also find that density of co-worker networks, and also their regional concentration decrease, if network information is available.
Keywords: C63; D85; J61; R12; 330; labor mobility; co-worker networks; regional inequality; knowledge spillovers; agent-based simulation